The poor bugger's tool Irish modernism, queer labor, and postcolonial history - Mullen, Patrick R. (New York ; Oxford : Oxford University Press, 2012)
'The Poor Bugger's Tool' - the title taking its name from the veiled reference to Roger Casement in Joyce's 'Ulysses' - draws on writings by Wilde, Synge, Joyce, Jamie O'Neill, and Patrick McCabe to consider how each deploys queer aesthetics to shape inclusive forms of national affiliation and put forward anti-imperialist critiques.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: English literature -- Irish authors -- History and criticism; English literature -- 20th century -- History and criticism; Homosexuality in literature; Queer theory; Value in literature; Values in literature; Postcolonialism in literature; Nationalism and literature -- Ireland -- History; Homosexuality and literature -- Ireland -- History; Modernism (Literature) -- Ireland